Control laws of a salient pole synchronous machine in a mine electric locomotive - Yuriy P. Filiushov; Alexander A. Voevoda; Vladislav Yu. Filyushov (Известия Томского политехнического университета: Инжиниринг георесурсов, 2023)
Relevance. The need to find effective control of a traction synchronous motor with permanent magnets in a mining electric locomotive under conditions of limitation of current and voltage supplied to its windings from an autonomous power source. Aim. To choose a control law that ensures an increase in a mine electric locomotive mileage on one battery charge with its speed growth. Object. Control laws of a salient pole synchronous motor with permanent magnets of a mining electric locomotive; laws of current control along the transverse axis; control by the current minimum and control by minimizing the reactive power of a salient pole synchronous machine. Methods. Analysis of the state of the electric machine with different formation of control of an electric drive in the mine electric locomotive. The main limiting indicators of an electric machine with voltage and current limitation were considered. For each control law, the results of mathematical modeling are shown in graphical and tabular form. Results. The analysis of the current control law along the transverse axis demonstrates a significant increase in reactive power with increasing load. In an hourly mode of operation, the reactive power exceeds the active power spent on the movement of the electric locomotive. When limiting the current and voltage, the minimum current control allows you to increase the electromagnetic torque by 12.7% in hourly operation. The maximum engine speed is increased by 13%. The maximum power spent on the electric locomotive movement increases by 33%. Reactive power is reduced by 29%. With reactive power minimization, despite the decrease in the electromagnetic torque in the hourly mode of operation by 4.8%, the maximum possible engine speed increases by 53%, the power spent on the electric locomotive movement increases by 50%.